Controlled Design of Well‐Dispersed Ultrathin MoS2 Nanosheets inside Hollow Carbon Skeleton: Toward Fast Potassium Storage by Constructing Spacious "Houses" for K Ions. (20th January 2020) - Cui, Yongpeng; Liu, Wei; Feng, Wenting; Zhang, Yuan; Du, Yongxu; Liu, Shuang; Wang, Huanlei; Chen, Ming; Zhou, Junan
Abstract: The large volume expansion induced by K + intercalation is always a big challenge for designing high‐performance electrode materials in potassium‐ion storage system. Based on the idea that large‐sized ions should accommodate big "houses, " a facile‐induced growth strategy is proposed to achieve the self‐loading of MoS2 clusters inside a hollow tubular carbon skeleton (HTCS). Meantime, a step‐by‐step intercalation technology is employed to tune the interlayer distance and the layer number of MoS2 . Based on the above, the ED‐MoS2 @CT hybrids are achieved by self‐loading and anchoring the well‐dispersed ultrathin MoS2 nanosheets on the inner surface of HTCSs. This unique compositing model not only alleviates the mechanical strain efficiently, but also provides spacious "roads" (hollow tubular carbon skeleton) and "houses" (interlayer expanded ultrathin MoS2 sheets) for fast K + transition and storage. As an anode of potassium‐ion batteries, the resultant ED‐MoS2 @CT electrode delivers a high specific capacity of 148.5 mAh g −1 at 2 A g −1 after 10 000 cycles with only 0.002% fading per cycle. The assembled ED‐MoS2 @CT//PC potassium‐ion hybrid supercapacitor device shows a high energy density of 148 Wh kg −1 at a power density of 965 W kg −1, which is comparable to that of lithium‐ion hybrid supercapacitors. Abstract : The self‐loading of uniform dispersion ultrathin MoS2 nanosheets on the inner surface of a hollow tubular carbon skeleton is achieved via the surface‐induced growth of MoS2 and step‐by‐step intercalation of double organic molecules. The proper structural design renders the as‐obtained ED‐MoS2 @CT materials a more comprehensive electrochemical ability in the potassium‐ion energy storage system.